Konsep Pencegahan dan Peningkatan Permukiman Kumuh: Studi Kasus: Permukiman Kumuh di Kawasan Cimpu, Kecamatan Suli, Kabupaten Luwu - Ibrahim Jabir B; Rudi Latief; Idris Taking (Journal of Urban Planning Studies, 2022)
The purpose of this study was to analyze the level of slums and formulate the concept of prevention and improvement of the quality of slum settlements in the Cimpu area, Suli District, Luwu Regency. This type of research is a mix method research. To analyze the level of slums in the Cimpu area, Suli sub-district, Luwu district using a baseline scoring analysis tool, while to formulate the concept of preventing and improving the quality of slum settlements in the Cimpu area, a technical design is used in the form of three dimensions (3D). The main conclusion in this study is that based on the results of the baseline scoring analysis, it shows that the level of slums in the Cimpu area, Suli District, Luwu Regency is in the medium slum category and the concept of prevention and improvement of slum settlements in the Cimpu Area, Suli District, Luwu Regency consists of two, namely prevention and improvement quality. The concept of prevention is implemented through a pattern of supervision, control, and community empowerment, while the concept of quality improvement is implemented through a pattern of restoration, rejuvenation, and resettlement